Pengaruh Standar Sarana dan Prasarana terhadap Motivasi Kerja Guru Daycare - Widyawati, Widyawati; Rizki Tiara, Dinda (Nak-Kanak: Journal of Child Research, 2024)
This study aims to determine the influence of facilities and infrastructure standards on the work motivation of daycare teachers. The research employs a quantitative approach, utilizing simple linear regression and correlation analysis. The study was conducted in Pamekasan Regency, encompassing all 30 daycare teachers through a saturated sampling technique. Data were collected via an online questionnaire using a Likert scale. Validity testing with 30 respondents revealed that the significance values for variables X and Y were 0.004 < 0.05, indicating the validity of all items for both variables. Reliability testing yielded a Cronbach's alpha coefficient of 0.931 for variable X and 0.852 for variable Y, both exceeding the 0.6 threshold, thus confirming the reliability of the items for both variables. Normality testing showed a significance value of 0.150 > 0.05, suggesting a normal distribution of residuals. Homogeneity testing resulted in a value of 0.601 > 0.05, indicating homogeneous data. The correlation test indicated a significance value of 0.004 < 0.05, demonstrating a correlation between the two variables. The simple linear regression analysis produced an F value of 9.608, which is greater than the F table value of 4.196, with a significance level of 0.004 < 0.05. This indicates that the standards of daycare facilities and infrastructure significantly influence the work motivation of daycare teachers. The correlation coefficient of 0.505 translates to 50.5%, suggesting that the facilities and infrastructure variable (X) accounts for 50.5% of the variance in the work motivation of daycare teachers (Y).